The role of Ursodeoxycholic acid in non-alcoholic steatohepatitis: a systematic review - Xiang, Zun; Chen, Yi-peng; Ma, Kui-fen; Ye, Yue-fang; Zheng, Lin; Yang, Yi-da; Li, You-ming; Jin, Xi (BMC gastroenterology, 2013)
Non-alcoholic steatohepatitis (NASH) is a condition that occurs during the progression of non-alcoholic fatty liver disease. Effective therapy for NASH is still lacking. In this study, we investigated the effects of Ursodeoxycholic acid (UDCA) in the treatment of NASH. Western and Chinese databases were searched by independent investigators using appropriate MESH headings to identify randomized, controlled Western and Chinese clinical trials, published between January 1990 and October 2012, testing the effects of UDCA in patients with NASH. Patient characteristics and trial endpoints were analyzed, with quality assessment according to widely acknowledged criteria. P < 0.05 was defined as statistically significant in all trials. Twelve qualified randomized clinical trials, including six from China and involving 1160 subjects, were selected. Seven of these trials assessed the effects of UDCA Monotherapy, with the other five testing combinations of UDCA with vitamin E, polyene phosphatidylcholine, silymarin, glycyrrhizin and tiopronin. The duration of therapy ranged from 3 to 24 months, with two studies using high doses of UDCA (23-35 mg/kg/d). The average quality point was 2.69, and was significantly lower in articles from China than in those from Western countries (2.2 ± 0.4 vs. 3.8 ± 1.1, respectively, p < 0.05). UDCA Monotherapy significantly improved liver function in five studies and improved steatosis and fibrosis in two studies. All five studies assessing UDCA combination therapy showed significant improvements liver function, while two studies also improved steatosis and inflammation. One study of high-dose UDCA showed significant improvements in ALT, γGT and liver fibrosis, whereas the other study showed no significant change in ALT and liver pathology. UDCA therapy is effective in NASH, especially when combined with other drugs. However, the low quality of these studies and the heterogeneity of their results precluded further meta-analysis. Additional carefully designed clinical trials are needed, especially in China.